2021
DOI: 10.7759/cureus.19728
|View full text |Cite
|
Sign up to set email alerts
|

Is White Blood Cell Count Associated With Mortality in Peritoneal Dialysis Patients?: A Retrospective Single-Center Analysis

Abstract: Objective White blood cell (WBC) count was used as a predictor in researches since it is a prognostic indicator and a substantial predictor of the development of cardiovascular disease (CVD). There have been very few reports looking at the association between WBC count and overall mortality in peritoneal dialysis (PD) patients. We intended to explore if the baseline total leukocyte count is linked to all-cause mortality, considering the association for linearity in PD patients. Material a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…WBC count has been reported to be a significant risk predictor for adverse events in patients undergoing PD [ 29 31 ]. One study reported a 23% increase in the risk of death for every 10 9 /L rise in WBC count in an approximate model [ 32 ]. The same trend was observed in our model, where the risk of mortality within six months increased by 8% for every 10 9 /L increase in the baseline WBC count in older patients treated with USPD.Interestingly, from the baseline laboratory data, WBC levels were found to be essentially within the normal range.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…WBC count has been reported to be a significant risk predictor for adverse events in patients undergoing PD [ 29 31 ]. One study reported a 23% increase in the risk of death for every 10 9 /L rise in WBC count in an approximate model [ 32 ]. The same trend was observed in our model, where the risk of mortality within six months increased by 8% for every 10 9 /L increase in the baseline WBC count in older patients treated with USPD.Interestingly, from the baseline laboratory data, WBC levels were found to be essentially within the normal range.…”
Section: Resultsmentioning
confidence: 99%
“…It has been noted that WBC counts in the middle or upper third of the normal range are associated with increased mortality [ 33 ], which suggests that WBC counts in the normal range may also offer clinically meaningful information. Higher WBC counts reflect the inflammatory state of the body [ 32 ]. Older patients are weaker against infections and more susceptible to sepsis due to decreased immunity and malnutrition [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in the pattern of total and differential leukocyte count have been observed when comparing adult CKD patients with non-CKD counterparts and pre-dialysis with dialysis adults [12][13][14][15][16][17]. The modulating role of platelets in CKD-related inflammatory pathways has also been reviewed [18].…”
Section: Introductionmentioning
confidence: 99%